Mistreatment of women during childbirth in West Bank, Palestine : development and validation of questionnaire, prevalence and associated factors, and its relationship with satisfaction and perceived quality of care - Ibtisam M M, Dwikat (2022)
Mistreatment during childbirth phenomenon should be understood among Palestinian women because it has not been adequately addressed in Palestine. This study aimed to measure the prevalence, types of mistreatment, associated factors and its association with satisfaction of care and perceived quality of care in West Bank, Palestine. It was conducted in two phases using a multi-method approach. Phase one involved the development and validation of questionnaire. Development of the questionnaire was achieved through literature review and qualitative study using face-to-face interviews with six purposively selected postpartum women and five healthcare providers to explore how women were treated during childbirth. Thematic analysis was conducted. Exploratory and confirmatory factor analysis was conducted for validation of satisfaction of care and perceived quality of care domains. This validation study involved 400 women attending maternal and child health clinics within the first 16 weeks postpartum who were selected using purposive sampling. For phase two, a cross sectional study was done among 269 women within the first 16 weeks postpartum from the six governorates located in north area of West Bank by using proportionate stratified random sampling. Multiple logistic regression analysis was used to determine factors associated with mistreatment. The associations of mistreatment with satisfaction of care and perceived quality of care wereanalysed using simple linear regression. The new questionnaire was designed in Arabic language and consisted of 87 items; experience of mistreatment during childbirth (43 items), satisfaction of care (10 items), perceived quality of care (16 items), and 18 items related to socio-demographic and obstetric characteristics. The Mistreatment, Satisfaction and Quality of Care Questionnaire (MSQ-Q) had good psychometric properties and reliability. The overall prevalence of mistreatment was 97.8%; with each type was 88.5% for poor rapport between women and providers, physical abuse (76.6%), failure to meet professional standard of care (75.8%), verbal abuse (24.5%), stigma and discrimination (11.9%), and health system conditions and constraints (22.3%). The significant factors associated with mistreatment during childbirth were age, type of labour, type of facility, mode of delivery, residency, duration of labour, education, pain killer received and parity. Women who experienced any types of mistreatment except physical abuse had significantly lower satisfaction of care and perceived quality of care scores. In conclusion, the majority of the participants encountered at least one type of mistreatment during childbirth. Women who delivered at public childbirth facility were more prone to face all the reported six types of mistreatment. Furthermore, the limitations in childbirth facilities, poor working environment, some recent policies such as preventing childbirth companion should be modified especially at public facilities to reduce mistreatment during childbirth.